A high-transparency stable super-hydrophobic coating constructed in multiple scales and a preparation method thereof
Patent Information
- Application Number
- CN202411638517.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-17
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-11-17
AI Technical Summary
[0004]本发明的目的在于提出一种多尺度构建的高透明稳定超疏水涂层及其制备方法,以解决上述背景技术中提出的现有涂层存在涂层脆弱、稳定性不足的技术问题
[0022] This invention introduces multi-scale coupling to prepare transparent superhydrophobic surfaces, specifically through the synergistic stacking of micron-sized hollow particles and nanoparticles. The micron-sized hollow particles provide support while maintaining transparency; the coupled nanoparticles, with a size of approximately 40 nm (less than one-tenth the wavelength of visible light), minimize the effects of Mie and Rayleigh scattering, thus maintaining high transparency. Simultaneously, surface stability is optimized to ensure that the superhydrophobic surface achieves excellent antifouling properties in practical applications without sacrificing transparency and mechanical strength.
Smart Images

Figure CN119608545B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of superhydrophobic materials technology, specifically relating to a highly transparent and stable superhydrophobic coating constructed at multiple scales and its preparation method. Background Technology
[0002] Currently, the mainstream approach for preparing transparent superhydrophobic coatings mostly utilizes nanoparticles with a size smaller than 100 nm. The self-similar structure formed by the stacking of nanoparticles exhibits excellent anti-wetting properties, thereby effectively improving the weather resistance of the coating. However, transparent superhydrophobic surface coatings formed by this nanoparticle stacking structure suffer from defects such as fragility and insufficient stability.
[0003] Researchers are dedicated to exploring various methods to achieve superhydrophobic surfaces that meet transparency requirements. Patent CN117925047A uses epoxy resin coupled with silane to prepare a transparent solvent, obtaining a transparent superhydrophobic coating through immersion or spraying. However, the coating obtained by this method contains organic resin, making it prone to aging and exhibiting poor weather resistance. Patent CN115404004A utilizes a silane coupling agent combined with silica to form a nanostructured stack, but its stability is poor, and the surface structure is difficult to maintain for long. Summary of the Invention
[0004] The purpose of this invention is to propose a highly transparent and stable superhydrophobic coating constructed at multiple scales and its preparation method, so as to solve the technical problems of existing coatings being fragile and lacking stability as mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution:
[0006] A method for preparing a highly transparent and stable superhydrophobic coating constructed at multiple scales, specifically including the following steps:
[0007] (1) Select polystyrene (PS) microspheres as hard templates, use alcohol solution as medium, add tetraethyl silicate or SiCl4, use acid or base as catalyst, form a silica shell on the surface of PS microspheres, and prepare PS@SiO2 particles.
[0008] (2) The PS@SiO2 particles obtained in step (1) are formulated into a PS@SiO2 aqueous dispersion; after the substrate is modified, it is immersed in the PS@SiO2 aqueous dispersion to obtain a single-layer PS@SiO2 coating on the substrate.
[0009] (3) After drying the coated substrate obtained in step (2) in air, place it in a muffle furnace and gradually raise the furnace temperature to the specified temperature according to the predetermined heating program. After reaching the specified temperature, keep it at the specified temperature and then let it cool naturally to room temperature.
[0010] (4) A layer of SiO2 is generated on the substrate surface obtained in step (3) by chemical vapor deposition;
[0011] (5) The substrate obtained in step (4) is immersed in SiO2 nanoparticle sol to form a micro-nano composite structure, and the nanoparticles are hydrophobically modified by gas / liquid phase method.
[0012] Further, in step (1), the alcohol is ethanol, the catalyst is concentrated ammonia, and the ratio of each substance in the reaction is: PS microspheres: ethanol: tetraethyl silicate: concentrated ammonia = 0.3g: 40ml: 0.2ml: 1.6ml, and the mass fraction of the concentrated ammonia is 25-28%.
[0013] Further, in step (2), the modification treatment refers to treating the substrate with a plasma cleaner to make it positively charged, then immersing the substrate in a toluene solution of amino-terminated silane coupling agent, and then using hydrochloric acid for protonation treatment; the concentration of the PS@SiO2 aqueous dispersion is 5 mg / ml.
[0014] Furthermore, in step (3), the predetermined heating program refers to raising the temperature to 400°C at a rate of 4-5°C / min and holding it at that temperature for 2 hours.
[0015] Further, in step (4), the chemical vapor deposition method refers to placing the substrate obtained in step (3) together with two glass bottles containing 4 ml of tetraethyl silicate and 4 ml of ammonia water into a vacuum jar and sealing them for 24 hours.
[0016] Furthermore, the alcohol is selected from any one of ethanol, propanol, isopropanol, acetone, and ethyl acetate, and the PS microspheres are submicron-sized particles with a size of 500-800 nm. The acid catalysts used for catalysis mainly include H2SO4, H3PO4, HCl aqueous solution, acetic acid, etc., and the base catalysts mainly include NaOH aqueous solution, KOH aqueous solution, ammonia water, etc.
[0017] Furthermore, the amino-terminated silane coupling agent is selected from any one of triaminopropyltriethoxysilane, triaminopropyltrimethoxysilane, and (3-aminopropyl)dimethylethoxysilane.
[0018] Furthermore, in step (5), the nanoparticles are hydrophobically modified by hydrolysis and condensation reaction with an organosilane coupling agent.
[0019] Furthermore, the organosilane coupling agent includes fluorinated organosilane coupling agents and non-fluorinated organosilane coupling agents; the non-fluorinated organosilane coupling agents include KH-550, KH-540, KH-902, and KH-554; the fluorinated organosilane coupling agents include perfluorodecyltrichlorosilane, perfluorohexyltrichlorosilane, perfluorooctyltrichlorosilane, perfluorododecyltrichlorosilane, perfluorohexyltrimethoxysilane, perfluorooctyltrimethoxysilane, perfluorodecyltrimethoxysilane, perfluorohexyltriethoxysilane, perfluorooctyltriethoxysilane, and perfluorodecyltriethoxysilane.
[0020] Another object of the present invention is to provide a highly transparent and stable superhydrophobic coating constructed by the above method at multiple scales.
[0021] The present invention has the following beneficial effects:
[0022] This invention introduces multi-scale coupling to prepare transparent superhydrophobic surfaces, specifically through the synergistic stacking of micron-sized hollow particles and nanoparticles. The micron-sized hollow particles provide support while maintaining transparency; the coupled nanoparticles, with a size of approximately 40 nm (less than one-tenth the wavelength of visible light), minimize the effects of Mie and Rayleigh scattering, thus maintaining high transparency. Simultaneously, surface stability is optimized to ensure that the superhydrophobic surface achieves excellent antifouling properties in practical applications without sacrificing transparency and mechanical strength. Attached Figure Description
[0023] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0024] Figure 1 A schematic diagram of the process for preparing PS@SiO2 particles;
[0025] Figure 2 A schematic diagram of the process to obtain a single-layer PS@SiO2 coating;
[0026] Figure 3 Scanning electron microscope image of submicron scale monolayer microspheres;
[0027] Figure 4 Image before pyrolysis;
[0028] Figure 5 Images after pyrolysis;
[0029] Figure 6 This is a scanning electron microscope image of the morphology after vapor deposition;
[0030] Figure 7 The image shows the morphology of the superhydrophobic coating under a scanning electron microscope.
[0031] Figure 8 Image showing the water contact angle of a superhydrophobic coating;
[0032] Figure 9 Comparison chart of results from temperature shock test, alternating damp heat test, salt spray test and anti-algae adhesion test;
[0033] Figure 10 This is the result of the light transmittance measurement. Detailed Implementation
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] See Figure 1-10 As shown, a highly transparent and stable superhydrophobic coating constructed at multiple scales and its preparation method specifically include the following steps:
[0036] Step 1: Preparation of PS@SiO2 particles.
[0037] Polystyrene (PS) microspheres were selected as templates, and tetraethyl or SiCl4 was added to the surface of the PS microspheres under the catalysis of acid or base in an alcohol solution.
[0038] The alcohols mentioned in this step are selected from any one of ethanol, propanol, isopropanol, acetone, and ethyl acetate; the polystyrene (PS) microspheres are submicron particles with a size of 500-800 nm; the acid catalysts used for catalysis are mainly H2SO4, H3PO4, HCl aqueous solution or acetic acid, etc., and the base catalysts are mainly NaOH aqueous solution, KOH aqueous solution or ammonia water, etc.
[0039] Taking an ethanol-medium, ammonia-catalyzed system as an example, PS microspheres are dissolved in an ethanol solution to form a PS sphere solution. Continuous stirring is used to achieve dispersion. Then, TEOS and concentrated ammonia (volume ratio 1:8) are added, and stirring is continued for 24 hours to complete the process. The reaction was followed by centrifugation to obtain PS@SiO2 particles. This process is as follows: Figure 1As shown. The proportions of the substances in the reaction are: PS microspheres: ethanol: tetraethyl silicate: concentrated ammonia = 0.3g: 40ml: 0.2ml: 1.6ml. The mass fraction of concentrated ammonia is 25-28%.
[0040] Step 2: Arrangement of PS@SiO2 particles on the substrate.
[0041] First, the particles obtained in step one were formulated into an aqueous dispersion of approximately 5 mg / ml PS@SiO2 for assembly and arrangement on a substrate. Next, the substrate was modified by treating it with a plasma cleaner to impart a positive charge. Then, the substrate was immersed in a toluene solution of an amino-terminated silane coupling agent for 30 minutes, followed by protonation treatment with hydrochloric acid. Finally, the positively charged substrate was immersed in the 5 mg / ml PS@SiO2 aqueous dispersion for 30 minutes to obtain a monolayer PS@SiO2 coating. This process is as follows: Figure 2 As shown. Figure 3 This is a scanning electron microscope image of the submicron scale monolayer arrangement of microspheres.
[0042] The amino-terminated silane coupling agent used in this step is selected from any one of triaminopropyltriethoxysilane, triaminopropyltrimethoxysilane, and (3-aminopropyl)dimethylethoxysilane.
[0043] Step 3: Pyrolysis improves coating transparency.
[0044] The introduction of micron-sized particles provides some support, but it will inevitably reduce the transparency of the coating. Therefore, it is necessary to make them transparent so that they form submicron-sized hollow particles arranged in an orderly manner on the substrate, which can both ensure transparency and provide support.
[0045] The coated substrate obtained in step two was dried in air and then placed in a muffle furnace. The temperature was increased to 400°C at a rate of 4-5°C / min and maintained at this temperature for 2 hours, after which the furnace was allowed to cool naturally to room temperature. After calcination, the PS@SiO2 particles became hollow microspheres, and the transparency of the coating was significantly improved. Figure 4 Image before pyrolysis. Figure 5 This is an image after pyrolysis.
[0046] Step four: Vapor deposition improves coating stability.
[0047] In-situ inorganic crosslinking was employed to further increase the adhesion between the hollow microspheres and the substrate, thereby enhancing their strength as a framework. In-situ growth and crosslinking were performed using chemical vapor deposition to grow silica.
[0048] The substrate obtained in step three was placed in a vacuum chamber along with two glass bottles containing 4 ml of tetraethyl orthosilicate (TEOS) and 4 ml of ammonia, respectively, for 24 hours of chemical vapor deposition (CVD) growth to form a layer of SiO2 on its surface, thereby improving the stability of the coating. Figure 6 This is a scanning electron microscope image of the vapor phase deposition.
[0049] Step 5, composite nanoparticles
[0050] The substrate obtained in step four was immersed in SiO2 nanoparticle sol for 10 min to form a micro-nano composite structure. The nanoparticles were then hydrophobically modified using a gas / liquid phase method, for example, by hydrolysis and condensation reaction between an organosilane coupling agent and the nanoparticles to achieve hydrophobic modification of the nanoparticles. Figure 7 Scanning electron microscope image of the highly transparent and stable superhydrophobic coating constructed at multiple scales. Figure 8 The image shows the water contact angle of the superhydrophobic coating, which is 152.9°, indicating excellent superhydrophobic properties.
[0051] The organosilane coupling agents mentioned in this step include fluorinated organosilane coupling agents and non-fluorinated organosilane coupling agents; non-fluorinated organosilane coupling agents include KH-550, KH-540, KH-902, and KH-554; fluorinated organosilane coupling agents include perfluorodecyltrichlorosilane, perfluorohexyltrichlorosilane, perfluorooctyltrichlorosilane, perfluorododecyltrichlorosilane, perfluorohexyltrimethoxysilane, perfluorooctyltrimethoxysilane, perfluorodecyltrimethoxysilane, perfluorohexyltriethoxysilane, perfluorooctyltriethoxysilane, and perfluorodecyltriethoxysilane.
[0052] To verify the coating performance, environmental tests were conducted, including temperature shock test, alternating damp heat test, salt spray test, and anti-algae adhesion test.
[0053] Temperature shock test: The coating was kept at 70℃±2℃ and -46℃±2℃ for 2 hours as one cycle. After 5 cycles and returning to room temperature, the water contact angle showed no significant change, and the film layer showed no defects such as peeling, delamination, cracking, or blistering. Alternating damp heat test: The transparent superhydrophobic coating was kept at 50℃±2℃ and 95%-100% relative humidity for 24 hours as one cycle. After 5 cycles and returning to room temperature, the water contact angle decreased by about 1°, and the film layer showed no defects such as peeling, delamination, cracking, or blistering. Salt spray test: 24 hours of salt spray followed by 24 hours of drying constituted one cycle, and 5 cycles were performed. The coating still exhibited superhydrophobicity. Anti-algae adhesion test: The sample was immersed in a Chlorella solution at an ambient temperature of 25℃, ensuring that the initial algae concentration was greater than 10%. 8 cm -3After five consecutive days of observation and experimentation, the blank control sample showed salt accumulation and seaweed adhesion on its surface at different time points (day 1, day 3, and day 5). In contrast, the transparent superhydrophobic sample did not show any salt accumulation or seaweed adhesion on its surface throughout the entire five-day test. Furthermore, the transparent superhydrophobic sample retained its superhydrophobic properties after five days of experimentation.
[0054] Figure 9 The chart shows a comparison of the results from temperature shock testing, alternating damp heat testing, salt spray testing, and anti-algae adhesion testing. It can be seen that after undergoing various environmental tests, including temperature shock testing, alternating damp heat testing, salt spray testing, and anti-algae adhesion testing, the coating still maintains its self-cleaning superhydrophobic properties, demonstrating excellent coating stability.
[0055] Figure 10 The transmittance measurement results are presented. According to the data shown in the figure, the overall transmittance loss of the transparent superhydrophobic coating is about 5%, which is relatively small compared to other transparent superhydrophobic coating preparation schemes with better stability.
[0056] This invention introduces multi-scale coupling to prepare transparent superhydrophobic surfaces, specifically employing a synergistic stacking of micron-sized hollow particles and nanoparticles. The micron-sized hollow particles, while ensuring transparency, also provide support and increased stability; the nanoparticle stacking provides both transparency and superhydrophobicity. The micron-structure uses microspheres as building blocks, utilizing their concave, controllable, and ordered arrangement to enhance hydrophobicity; the hollow structure of the microspheres improves light transmittance; and physical cross-linking strengthens the bond between the particles and the substrate, improving stability. The nanoparticles, with diameters of around tens of nanometers, reduce scattering and improve light transmittance; the controllable stacking of the nanostructure enhances superhydrophobicity; and the self-similar structure of the nanostructure improves weather resistance.
[0057] The unique properties of the superhydrophobic structure of this invention can effectively prevent the adhesion of contaminants, thereby ensuring the clarity and durability of critical components. This superhydrophobic structure can be used on surfaces with high transparency requirements, such as automotive windshields, solar panels, camera lenses, and marine optical windows.
[0058] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention.
Claims
1. A method for preparing a highly transparent and stable superhydrophobic coating constructed at multiple scales, characterized in that, The method employs a synergistic stacking of micron-sized hollow particles and nanoparticles; the coupled nanoparticles are smaller than one-tenth the wavelength of visible light, and specifically includes the following steps: (1) Select polystyrene microspheres as templates, use alcohol solutions as media, add tetraethyl silicate or SiCl4, use acid or base as catalysts, form a silica shell on the surface of PS microspheres, and prepare PS@SiO2 particles. (2) The PS@SiO2 particles obtained in step (1) are formulated into a PS@SiO2 aqueous dispersion; after the substrate is modified, it is immersed in the PS@SiO2 aqueous dispersion to obtain a single-layer PS@SiO2 coating on the substrate; the modification treatment refers to treating the substrate with a plasma cleaner to make it positively charged, then immersing the substrate in a toluene solution of amino-terminated silane coupling agent, and then protonating it with hydrochloric acid; (3) After drying the coated substrate obtained in step (2) in air, place it in a muffle furnace and gradually raise the furnace temperature to the specified temperature according to the predetermined heating program. After reaching the specified temperature, keep it at the temperature for 2 hours, and then let it cool naturally to room temperature. The predetermined heating program refers to raising the temperature to 400°C at a rate of 4-5°C / min and keeping it at the temperature. (4) A layer of SiO2 is generated on the substrate surface obtained in step (3) by chemical vapor deposition; (5) The substrate obtained in step (4) is immersed in SiO2 nanoparticle sol to form a micro-nano composite structure, and then the nanoparticles are hydrophobically modified by gas / liquid phase method.
2. The method for preparing a highly transparent and stable superhydrophobic coating constructed at multiple scales according to claim 1, characterized in that, In step (1), the alcohol is ethanol, the catalyst is concentrated ammonia, and the ratio of each substance in the reaction is: PS microspheres: ethanol: tetraethyl silicate: concentrated ammonia = 0.3g: 40ml: 0.2ml: 1.6ml, and the mass fraction of the concentrated ammonia is 25%-28%.
3. The method for preparing a highly transparent and stable superhydrophobic coating constructed at multiple scales according to claim 1, characterized in that, In step (2), the concentration of the PS@SiO2 aqueous dispersion is 5 mg / ml.
4. The method for preparing a highly transparent, stable, superhydrophobic coating constructed at multiple scales according to claim 1, characterized in that, In step (4), the chemical vapor deposition method refers to placing the substrate obtained in step (3) together with two glass bottles containing 4 ml of tetraethyl silicate and 4 ml of ammonia water into a vacuum jar for sealing.
5. The method for preparing a highly transparent and stable superhydrophobic coating constructed at multiple scales according to claim 1, characterized in that, The alcohols are selected from any one of ethanol, propanol, isopropanol, acetone, and ethyl acetate. The PS microspheres are submicron particles with a size of 500-800 nm. The acid catalysts used for catalysis include H2SO4, H3PO4, HCl aqueous solution, or acetic acid. The base catalysts include NaOH aqueous solution, KOH aqueous solution, or ammonia.
6. The method for preparing a highly transparent, stable, superhydrophobic coating constructed at multiple scales according to claim 1, characterized in that, The amino-terminated silane coupling agent is selected from any one of triaminopropyltriethoxysilane, triaminopropyltrimethoxysilane, and (3-aminopropyl)dimethylethoxysilane.
7. The method for preparing a highly transparent and stable superhydrophobic coating constructed at multiple scales according to claim 1, characterized in that, In step (5), the nanoparticles are hydrophobically modified by hydrolysis and condensation reaction with organosilane coupling agent.
8. The method for preparing a highly transparent and stable superhydrophobic coating constructed at multiple scales according to claim 7, characterized in that, The organosilane coupling agents include fluorinated organosilane coupling agents and non-fluorinated organosilane coupling agents; non-fluorinated organosilane coupling agents include KH-550, KH-540, KH-902 or KH-554; fluorinated organosilane coupling agents include perfluorodecyltrichlorosilane, perfluorohexyltrichlorosilane, perfluorooctyltrichlorosilane, perfluorododecyltrichlorosilane, perfluorohexyltrimethoxysilane, perfluorooctyltrimethoxysilane, perfluorodecyltrimethoxysilane, perfluorohexyltriethoxysilane, perfluorooctyltriethoxysilane or perfluorodecyltriethoxysilane.
9. A highly transparent, stable, superhydrophobic coating with multi-scale construction prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation and application of transparent super-hydrophobic coating
CN115404004A
Transparent super-hydrophobic coating as well as preparation method and application thereof
CN117925047A
Silicon dioxide hollow sphere / polystyrene composite heat insulating material and method for preparing same
CN101585948A
Method for preparing transparent superhydrophobic surface
CN108623188A
Membrane preparation method combining construction of nanoparticles and membrane surface microstructure
CN113171689A